Pengembangan Perangkat Pembelajaran Bercirikan CTL Berbantuan GeoGebra Menggunakan Model Flipped Learning - Zuli Nuraeni; Indaryanti Indaryanti; Novika Sukmaningthias (Jurnal Elemen, 2021)
The purpose of this study was to develop valid, practical, and effective learning using the GeoGebra-assisted Contextual Teaching Learning (CTL) learning model using the Flipped Learning model to improve the mathematical representation abilities of junior high school students. This research is research and development (RD). This research has five stages: analyzing the developed product, developing the initial product, expert validation and revision, small-scale field trials and product revisions, and testing large-scale field and final products. Based on the results of several studies, including lesson plans and valid textbooks. From the limited test, the ten questions of the representation ability test were also valid and reliable. The lesson plans and textbooks developed are also practical in terms of teachers and students. Moreover, the average value of the mathematical representation in the experimental class is classified as effective in increasing students' mathematical representation ability. That way, the mathematics learning device characterized by GeoGebra assisted CTL using the Flipped Learning model can be said to be valid, practical, and effective.